Status of CHADS2 and CHA2DS2-VASc Scores in Predicting Risk of Stroke and its Prevention in Iraqi Patients with Atrial Fibrillation - Mohanad Y. Al-Radeef (College of Pharmacy University of Baghdad, 2019)
Atrial fibrillation is associates with elevated risk of stroke. The simplest stroke risk assessment schemes are CHADS2 and CHA2DS2-VASc score. Aspirin and oral anticoagulants are recommended for stroke prevention in such patients. The aim of this study was to  assess status of CHADS2 and CHA2DS2-VASc scores in Iraqi atrial fibrillation patients and to report current status of stroke prevention in these patients with either warfarin or aspirin in relation to these scores. This prospective cross-sectional study was carried out at Tikrit, Samarra, Sharqat, Baquba, and AL-Numaan hospitals from July 2017 to October 2017. CHADS2 and CHA2DS2-VASc scores were manually calculated. One hundred patients were participated, 48 were men and 52 were women. Their mean age was 62.56 ± 14.36 years. Permanent type of atrial fibrillation, palpitation, and hypertension were the most diagnosed type, symptom and comorbidity recorded in this study respectively. Average scores of CHADS2 and CHA2DS2-VASc were 2.34 ± 1.39 and 4.1 ± 2.05, respectively. These scores were not calculated for these patients in hospital setting. Aspirin and warfarin were prescribed regardless to these scores. The result of this study indicated that CHADS2 and CHA2DS2-VASc scores were often neglected in hospitals; and aspirin is still widely used as a strategy to minimize the risk of stroke. Keywords: Atrial fibrillation, CHADS2, CHA2DS2-VASc, aspirin, warfarin.